O007/#456 Post-hoc analysis of objective response rate by mismatch repair protein dimer loss/mutation status in patients with mismatch repair deficient endometrial cancer treated with dostarlimab. (4th December 2022) - Tinker, Anna; Sabatier, Renaud; Gravina, Adriano; Gilbert, Lucy; Brown, Jubilee; Samouëlian, Vanessa; Reade, Clare; Mathews, Cara; Ellard, Susan; Banerjee, Susana; Barretina-Ginesta, Maria Pilar; Miller, Rowan; et al.
Abstract : Objectives: Mismatch repair (MMR) deficiency is caused by loss of expression of MMR proteins, MLH1, PMS2, MSH2, and/or MSH6, that function as heterodimers (MLH1/PMS2 and MSH2/MSH6) to mediate DNA repair. Loss of function caused by mutation or epigenetic methylation leads to defective MMR and genomic instability. MMR deficient (dMMR) tumors can respond to anti-programmed death 1 (PD-1) therapy. We report on a post-hoc analysis of ORR with loss of MMR dimers and mutation status of MMR genes in patients with dMMR endometrial cancer (EC) treated with dostarlimab. Methods: GARNET is a multicenter, open-label, single-arm phase 1 study. Cohort A1 enrolled patients with dMMR advanced/recurrent EC. Patients received 500 mg dostarlimab intravenously Q3W for 4 cycles, then 1000 mg Q6W until disease progression, discontinuation, or withdrawal. MMR protein status (presence or loss) was determined by local IHC. MMR gene mutation was determined by Foundation One. MLH1 loss without MMR gene mutation was a surrogate indicator for epigenetic methylation. Results: Cohort A1 included 143 patients; MMR gene mutation data was available for 101 ( table 1 ). Cohort A1 ORR was 45.5%. 66% of patients had loss of MLH1/PMS2; ORR was 48.9%. 11.2% of patients had loss of MSH2/MSH6; ORR was 56.2%. ORR was 41.7% for MLH1 loss with MMR gene mutation and 39.4% for MLH1 loss without MMR gene mutation. Conclusions: Patients with dMMR advanced/recurrent EC benefitted from dostarlimab, with no noticeable difference by dimer-pair loss or MMR gene methylation/mutation status. These data suggest route to MMR deficiency does not influence response to dostarlimab.